Exercise-Induced Laryngeal Obstruction: When Pediatric Exertional Dyspnea Does not Respond to Bronchodilators - Olin, J. Tod (Frontiers in Pediatrics, 2019)
Exertional dyspnea is a common complaint in general pediatric practice. While a high proportion of the general pediatric population has asthma, other diagnoses, including exercise-induced laryngeal obstruction should be considered, especially when asthma therapy is not sufficient to control symptoms. This review describes some of the key clinical features of exercised-induced laryngeal obstruction as well as preferred diagnostic and therapeutic approaches. Importantly, current diagnostic technology has considerably improved in the last decade at specialty centers. At the same time, infrastructure for clinical trials is emerging and there is not strong evidence to support specific therapies at the current time.